PERMASALAHAN KEBISINGAN DI KOTA DENPASAR - Suarna, I W.; Kusuma K., C.I.P.; Sara Wijana, I M. (Bumi Lestari, 2012)
Research on the condition of air pollution in Denpasar City was carried out in the mid of 2007. Aims of this activity was to find out noise levels which occured on different sites with different uses, so the solution for the problems can be found out and the impact can be minimised. Data on noise levels were measured by using sound level metres, while sampling sites were determined by GPS, so replication can be exactly made on the same sampling locations. Fivty measurements were made on the sites where impacts of noise encountered by activities surrounding them. Results of the study showed that on the schools, settlements, and open-green area the noise levels have exceeded the benchmarks. As a result, some efforts need to be carried out , such as improvements of roads, and planting more trees which were not only used to minimized noise levels but also can improve aestetic levels of the city.
Keywords: noise, benchmark, spatial use, environment